Penyusunan Faktor Koreksi Produksi Susu Sapi Perah - Setya Agus Santosa; Anjang Taruno Ari Sudewo; Agus Susanto (Agricultural Faculty, 2014)
(Creating milk production correction factors of dairy cattle)ABSTRACT. The aim of the research was to obtain the correction factors of non-genetic effects that have influence on milk production of dairy cows. The research used a survey method on milk records of dairy cows kept in Dairy Cattle Breeding Center (BBPTU) of Baturraden. The data taken was only those relevant with the research objective. The data examined were as many as 324 production records of 108 dairy cows which had completed first three lactation, originated from 36 sires. Non-genetic factors studied were season, lactation period, number of days in milk of a lactation and age at birth. The effects of non-genetic factors were estimated through Stepwise multiple regression method. Effect of the number of days in milk of a lactation was highly significant (P 0.01), age at birth was significant (P 0.05), and season and the lactation period were not significant (P0.05) on milk production of dairy cows. Variables that have effect on milk production were then assigned the correction factors. Correction factors were derived from the least square mean (LSM) of the actual milk production. The correction factors were obtained by comparing the base LSM to the created LSM values on particular classes. The corrected milk production was obtained by multiplying the corresponding correction factor obtained with the actual milk production. Based on the study, the local correction factors lower the milk production variability of dairy cows.